2016
DOI: 10.1177/1471301216672489
|View full text |Cite
|
Sign up to set email alerts
|

An occupational perspective of the lived experience of familial dementia caregivers: A thematic review of qualitative literature

Abstract: Dementia caregiving is thought to have a negative impact on health and wellbeing. This critical review of qualitative literature explored the lived experience of familial dementia caregivers from an occupational therapy perspective. The method was informed by systematic review and qualitative research methodologies and was structured within the occupational dimensions framework of doing-being-becoming-belonging. A comprehensive search of major databases was undertaken which identified 484 studies on the topic;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Finally, relatives of persons with MND in both countries expressed fears of becoming a caregiver. This is not surprising, as there is a universal understanding that assuming a caregiver rolea realistic possibility for relatives of persons with MND (Carlozzi et al, 2018;Seeher et al, 2013) is a stressful experience, impacting the caregiver's quality of life and wellbeing (Cross et al, 2018;Hooper and Collins, 2019). Interestingly, in a recent quantitative study conducted among 2,609 Asian American LP, aged 18-98, around a quarter of the participants expressed similar concerns (Jang et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Finally, relatives of persons with MND in both countries expressed fears of becoming a caregiver. This is not surprising, as there is a universal understanding that assuming a caregiver rolea realistic possibility for relatives of persons with MND (Carlozzi et al, 2018;Seeher et al, 2013) is a stressful experience, impacting the caregiver's quality of life and wellbeing (Cross et al, 2018;Hooper and Collins, 2019). Interestingly, in a recent quantitative study conducted among 2,609 Asian American LP, aged 18-98, around a quarter of the participants expressed similar concerns (Jang et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Recent literature has explored and confirmed that caregiving has significant impacts on family members (Hooper & Collins, 2016) as family caregivers often put their own health needs secondary to their care recipients, resulting in deterioration of their own health and quality of life (Elliott, Burgio & DeCoster, 2010). It has been reported that 39% of family caregivers experience depression (Alzheimer's Association, 2014;Givens, Mezzacappa, Heeren, Yaffe & Fredman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These were interventions that could be carried out by any professional group. This is corroborated by two further reviews (Hooper and Collins, 2016; Yong and Price, 2014), both of which suggested that occupational therapists could offer interventions to achieve better outcomes for family caregivers and their loved ones.…”
Section: Literature Reviewmentioning
confidence: 70%
“…(2017) examined how families in the UK sustain the sense of autonomy and control in their loved ones’ lives through engagement in everyday activities. International occupational therapy qualitative studies by Hasselkus and Murray (2007) (United States of America (USA)), Hogan et al. (2003) (USA) and Persson and Zingmark (2006) (Sweden) have explored family/relative caregiver experiences, but each provided a different occupational emphasis in their findings.…”
Section: Literature Reviewmentioning
confidence: 99%